2012
DOI: 10.1370/afm.1376
|View full text |Cite
|
Sign up to set email alerts
|

Meditation or Exercise for Preventing Acute Respiratory Infection: A Randomized Controlled Trial

Abstract: PURPOSE This study was designed to evaluate potential preventive effects of meditation or exercise on incidence, duration, and severity of acute respiratory infection (ARI) illness.METHODS Community-recruited adults aged 50 years and older were randomized to 1 of 3 study groups: 8-week training in mindfulness meditation, matched 8-week training in moderate-intensity sustained exercise, or observational control. The primary outcome was area-under-the-curve global illness severity during a single cold and infl u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
158
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(166 citation statements)
references
References 53 publications
5
158
0
3
Order By: Relevance
“…The parent study, from which the current data were derived, showed that both exercise and MBSR reduced the number of days sick from all-cause acute respiratory infection (ARI) illness. 23 The incidence, duration and global severity of ARI illness episodes were decreased by 33-35% and 31-60%, among those assigned to MBSR and exercise training as compared with control. Nevertheless, the influenza vaccine generated similar, and what would be considered protective and clinically effective responses in most participants in this study cohort.…”
Section: Discussionmentioning
confidence: 91%
“…The parent study, from which the current data were derived, showed that both exercise and MBSR reduced the number of days sick from all-cause acute respiratory infection (ARI) illness. 23 The incidence, duration and global severity of ARI illness episodes were decreased by 33-35% and 31-60%, among those assigned to MBSR and exercise training as compared with control. Nevertheless, the influenza vaccine generated similar, and what would be considered protective and clinically effective responses in most participants in this study cohort.…”
Section: Discussionmentioning
confidence: 91%
“…Some of the most encouraging RCT research in the mindfulness intervention-physical health literature focuses on whether mindfulness interventions affect clinically-relevant measures of health and disease. An initial large RCT (N=154) showed that MBSR may reduce the number of self-reported illness days (and illness duration) over the course of a cold/flu season relative to a no treatment group (Barrett et al 2012). However, MBSR showed no relative advantage on illness-related outcomes compared to a moderate aerobic exercise program in this trial, although there was some evidence that MBSR reduced the total number of acute respiratory infection-related work days missed (16 days), more so than the aerobic exercise (32 days) and no treatment control (67 days) groups.…”
mentioning
confidence: 99%
“…While it is known that people can influence the functioning of their immune system through exercise, meditation, breathing techniques, and exposure to cold, we believe it is unlikely the interventions of the randomized clinical trial could significantly influence PCT measurements (2,8).…”
Section: Participantsmentioning
confidence: 90%